About the experience of building of law-abiding state in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2021)
This article discusses the experience and problems of building of law-abiding state. The idea of law-abiding state was born by the liberal trend of Western (bourgeois) political and legal thought. Historically, this idea combined the concept of inalienable natural human rights with the concept of the state - the «night watchman» of these rights. From the position of the legal essence of the rule of law, the public power of the latter excludes arbitrariness and acts only in accordance with the law, understood as a measure of freedom, normatively fixed justice. It is assumed that laws should be constantly checked for compliance with the law, its principles and the legal system. The main provisions of the concept of law-abiding state include: the supremacy of civil society over the state, the subordination of the state to the control of civil society; the primacy of law over politics and law; the supremacy of law over an administrative act and administrative discretion; the clear separation of the legislative, executive and judicial authorities; freedom of activity of individuals and their associations on the principle of «everything that is not prohibited is allowed»; guarantee of the protection of the interests of a minority; direct legal effect of the constitutional norms; jurisdiction of the court of any dispute about law.Key words: division of powers, human rights and freedoms, legislation, justice, civil society, law, justice, legal system, system of checks and balances, right.